Global resources forestry assessment 2005 (Rome : FAO, 2007)
The CD-ROM contains the key findings and the main report of the Glob al Forest Resources Assessment 2005. It also contains all country repo rts, specifications and guidelines, global result tables in Excel forma t, maps, graphs and a PowerPoint presentation
Keywords: Forest management -- Environmental aspects